Preparation method and application of anti-ultraviolet breathable fabric

By preparing composite particles with titanium dioxide particles as the core and porous silica as the shell, and hybridizing the polyurethane chain segments during electrospinning, the problem of insufficient performance of existing UV-resistant and breathable fabrics is solved, and efficient UV resistance is achieved Performance and excellent breathability.

CN119308135BActive Publication Date: 2025-02-18BIEM L FDLKK GARMENT CO LTD

Patent Information

Application Number
CN202411856940.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The breathable and UV-resistant properties of existing UV-resistant fabrics need to be further improved, and the introduced UV-resistant particle dispersion performance is poor, and it cannot cross-link with the material, which is prone to wear.

Method used

By preparing composite particles with titanium dioxide particles as the core and porous silica as the shell, and after modifying the active functional groups on their surface, hybrid polyurethane segments are integrated to enhance the conductive ability of the material during electrospinning, and at the same time, using modified composites Particles act as nucleation centers to promote self-assembly of silk fibroin to form spherical materials, and form stable void structures through microwave evaporation.

Benefits of technology

It significantly improves the wear resistance and UV resistance of the material, while also improving breathability and mechanical properties, enhancing the skin-friendliness and UV resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an anti-ultraviolet breathable fabric, belongs to the technical field of fabric processing, and is used to solve the technical problem that the air permeability and anti-ultraviolet performance of the fabric in the prior art need to be further improved; the invention comprises the following steps: immersing the modified fabric in a skin-friendly impregnation liquid, obtaining an impregnation material after impregnation and rolling, and obtaining the breathable fabric by a microwave evaporation process, wherein the composite particles are prepared with titanium dioxide particles as cores and porous silicon dioxide as shells, and active functional groups of epoxy groups are modified on the surface of the composite particles, and then polyurethane segments are hybridized, and the composite particles are used as nucleation centers to promote the self-assembly of silk fibroin to form spherical materials, and the titanium dioxide particles inside the composite particles act as ultraviolet absorbers and at the same time act as microwave absorption centers and electrostatic spinning conductive networks, thereby improving process efficiency, and the spherical materials are used as the main components of the skin-friendly impregnation liquid to form cross-links with the modified fabric to obtain the breathable fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric processing, and in particular to a preparation method of an anti-ultraviolet breathable fabric and application thereof. Background Art

[0002] The development of anti-ultraviolet breathable fabrics has gone through the stages from functional improvement to multifunctional composite. The initial research focused on coating and dyeing and finishing technology. The anti-ultraviolet function was achieved by applying ultraviolet absorbers or reflectors on the fabric surface. However, this method easily affects the breathability and comfort. The subsequent application of nanotechnology became a breakthrough point. The ultraviolet absorber was nano-sized and combined with the fiber, which not only enhanced the anti-ultraviolet performance but also retained the breathability of the fabric. In addition, through the research and development of functional fibers, such as fibers with embedded ultraviolet shielding components, the problem of easy coating shedding is solved. The recent development focuses on environmental protection and intelligence, developing green preparation technology and smart fabrics with adjustable ultraviolet protection, taking into account breathability and eco-friendliness, and meeting the diverse needs of outdoor clothing and protection fields.

[0003] However, traditional processing for the anti-ultraviolet performance of breathable fabrics mostly uses anti-ultraviolet liquid for soaking or introduces anti-ultraviolet silver oxide and titanium dioxide particles as ultraviolet absorption centers to improve the anti-ultraviolet performance of the material. However, the fabric modified with anti-ultraviolet liquid has weak durability and will cause certain blockage of the air pores, reducing the air permeability of the material. In addition, the introduced silver oxide particles and titanium dioxide particles are mostly added to the fabric in the form of fillers. The anti-ultraviolet particles introduced by this method have poor dispersion performance and cannot be cross-linked with the material. In addition, the surface lacks protection and is prone to wear, resulting in the anti-ultraviolet performance of the material needs to be further improved.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an anti-ultraviolet breathable fabric and its application, so as to solve the technical problem in the prior art that the air permeability and anti-ultraviolet performance of the fabric need to be further improved.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing an anti-ultraviolet breathable fabric comprises the following steps:

[0008] S1, adding modified polyurethane, saturated sodium hydroxide solution and N,N-dimethylformamide into a reactor and stirring, after the temperature of the reactor is raised to 60-80°C, adding modified composite particles into the reactor, keeping the temperature for reaction for 20-30 minutes, adding anti-ultraviolet liquid into the reactor, keeping the temperature for reaction for 10-20 minutes, and post-treating to obtain composite polyurethane;

[0009] The reaction principle for preparing composite polyurethane is as follows: under the catalysis of high temperature and alkaline conditions, the hydroxyl group at the end of the modified polyurethane reacts with the epoxy group on the surface of the modified composite material to form a stable cross-linked structure. As the reaction continues, the organic chain segments form a spatial structure with the modified composite particles as the core. Finally, the hydroxyl group on the 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole in the anti-ultraviolet liquid further reacts with the residual epoxy group on the modified composite particles to introduce the anti-ultraviolet group into the organic structure, and finally the composite polyurethane is obtained.

[0010] S2, adding composite polyurethane, auxiliary materials and N,N-dimethylformamide into a reaction kettle and stirring, stirring at room temperature for 10-15 minutes to obtain a spinning solution, and using the spinning solution for electrospinning to obtain modified polyurethane fibers;

[0011] S3, using the modified polyurethane fiber for weaving to obtain a modified fabric;

[0012] S4, soaking the modified fabric in a skin-friendly impregnation liquid, obtaining an impregnated material after impregnation and rolling, and obtaining a breathable fabric by a microwave evaporation process.

[0013] The reaction principle for preparing breathable fabrics is as follows: after the modified fabrics are immersed in the skin-friendly impregnation solution, the globular silk fibroin in the skin-friendly impregnation solution is evenly dispersed in the fabric structure, and the titanium dioxide particles are used as the heating center through microwave heating, and the solvent is evaporated from the inside out, so that the material forms a stable void structure, and a large number of active functional groups on the silk fibroin, such as amino and carboxyl groups, are continuously cross-linked with the active functional groups of epoxy groups on the surface of the material during the heating and evaporation process to form a stable structure, and finally a breathable fabric is prepared;

[0014] The preparation method of modified polyurethane comprises the following steps:

[0015] A1. Add UV absorber UV-13, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stir for 15-20 minutes at room temperature to obtain a prepolymer solution;

[0016] A2, adding the prepolymer liquid into the reactor, raising the temperature of the reactor to 50-60°C, dropping 1,3-di(isocyanatomethyl)benzene solution into the reactor, keeping the temperature for reaction for 40-60min, and post-treating to obtain modified polyurethane;

[0017] The reaction equation for preparing modified polyurethane is:

[0018]

[0019] Where: , the asterisk indicates the connection site between R1 and the benzene ring.

[0020] The reaction principle for preparing modified polyurethane is as follows: under the action of heating and catalyst, the hydroxyl group on the ultraviolet absorber UV-13 reacts with the isocyanate group on 1,3-di(isocyanatomethyl)benzene, and the reaction process is adjusted by controlling the amount of substance, and finally a modified polyurethane with hydroxyl group as the end cap is prepared.

[0021] The preparation method of the modified composite particles comprises the following steps:

[0022] B1. Add butyl titanate and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 50-60°C, use 1-2 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep the temperature for 36-48 hours to obtain titanium gel, and then post-treat to obtain titanium dioxide particles.

[0023] B2. Add titanium dioxide particles, tetraethoxysilane and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep the temperature for 24-36 hours to obtain a silicon-based gel, and then perform post-treatment to obtain composite particles.

[0024] B3. Add the composite particles, ethanol, saturated sodium hydroxide solution and deionized water into a reactor and introduce nitrogen protection. After the temperature of the reactor is reduced to 5-10°C, add 3-(2,3-epoxypropoxy)propyltrimethoxysilane into the reactor, keep the temperature for 20-30 minutes, and post-treat to obtain modified composite particles.

[0025] The reaction principle for preparing the modified composite particles is as follows: after titanium dioxide particles are prepared by hydrolysis, a large number of hydroxyl groups are avoided as the core through the titanium dioxide particles, so that tetraethoxysilane is hydrolyzed to form a stable cross-linked network on the surface of the titanium dioxide particles, and the strong absorption ability of titanium dioxide particles to microwaves is utilized. Microwave evaporation is used with titanium dioxide as the thermal core to evaporate the solvent inside the silicon dioxide cross-linked network, and finally a porous silicon dioxide protective layer is formed on the titanium dioxide surface to obtain composite particles, and the surface of the composite particles is modified by a silane coupling agent, and finally modified composite particles with a large number of epoxy groups cross-linked on the surface are prepared.

[0026] Further, in step S1, the amount ratio of modified polyurethane, saturated sodium hydroxide solution, N,N-dimethylformamide, modified composite particles and anti-ultraviolet liquid is 8-10g:0.5-0.8mL:25-30mL:2-3g:3-5mL, the stirring rate of the reactor is 80-120rpm, the anti-ultraviolet liquid is prepared by 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and N,N-dimethylformamide at a ratio of 1g:10mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a composite polyurethane;

[0027] Furthermore, in step S2, the stirring rate of the reactor is 80-120rpm, the amount ratio of the composite polyurethane, auxiliary materials and N,N-dimethylformamide is 12-15g:3.5g-5.4g:70-80mL, the auxiliary materials include modified composite particles, antibacterial agents, reinforcing agents and plasticizers, the amount ratio of the composite particles, antibacterial agents, reinforcing agents and plasticizers is 2-3g:0.5-0.8g:0.5-0.8g:0.5-0.8g, and the electrospinning operation includes: pouring the spinning solution into the ejector of the electrospinning machine, setting the voltage of the electrospinning machine to 20-25kV, setting the spinning distance to 20-30cm, controlling the flow rate at 0.8-1L / h, and spinning to obtain modified polyurethane fibers.

[0028] Furthermore, the antibacterial agent is one or more of benzalkonium chloride, polyhexamethylene guanidine and tetradecyltrimethylammonium chloride; the reinforcing agent is one or more of nano-silicon dioxide, carbon fiber and nano-alumina; and the plasticizer is one or more of dibutyl phthalate, triethyl citrate and dioctyl adipate.

[0029] Further, in step S3, the weaving operation includes: selecting 100-125D modified polyurethane fiber, the number of monofilaments is 36-48F, setting the twist of the yarn to 500-600 twists / m, the twist direction is Z twist, and after the twisting is completed, heat setting is performed at a temperature of 180-200°C, and winding is performed at a speed of 600-700m / min to obtain the yarn, and the yarns are used as warp yarns and weft yarns respectively, and the modified polyurethane layer is woven; the imperial count of the warp yarn is 36-42s, the imperial count of the weft yarn is 35-45s, and the density of the modified polyurethane layer is 160-180 warp yarns and 100-120 weft yarns per square inch.

[0030] Furthermore, in step S4, the dipping and rolling operation is a two-dipping and two-rolling process, the bath ratio is 1:20-25, the dipping and rolling rate is 90-110%, and the microwave evaporation process is: the impregnated material is transferred to a vacuum microwave device, the vacuum degree of the device is set to 50-200mbar, the power is 400-600W, the evaporation temperature is 40-50°C, and the breathable fabric is obtained by evaporating until no liquid is extracted.

[0031] Furthermore, in step A1, the amount ratio of ultraviolet absorber UV-13, N,N-dimethylformamide and dibutyltin dilaurate is 4-5g:25-30mL:0.1-0.3g, and the stirring rate of the reactor is 80-120rpm; in step A2, the amount ratio of the prepolymer solution and the 1,3-di(isocyanatomethyl)benzene solution is 20-25mL:12-15g, and the 1,3-di(isocyanatomethyl)benzene solution is prepared by 1,3-di(isocyanatomethyl)benzene and N,N-dimethylformamide in a weight ratio of 1:1, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified polyurethane.

[0032] Furthermore, in step B1, the stirring rate of the reactor is 80-120rpm, the dosage ratio of butyl titanate, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL, and the post-treatment includes: adding the titanium gel to a tubular furnace, after nitrogen protection, heating the tubular furnace to 750-850°C at a heating rate of 3-5°C / min, and calcining for 4-6h, and then grinding the material through a 600-800 mesh sieve to obtain titanium dioxide particles.

[0033] Further, in step B2, the amount ratio of titanium dioxide particles, tetraethoxysilane, anhydrous ethanol and deionized water is 1-2g:3-6g:30-40mL:10-20mL, the stirring rate of the reactor is 60-80rpm, and the post-treatment includes: transferring the silicon-based gel to a vacuum microwave device, setting the vacuum degree of the device to 50-200mbar, the power to 400-600W, the stirring rate to 50-60rpm, and controlling the temperature to 60-80°C, evaporating until no liquid is collected, and grinding. The material is sieved through a 400-600 mesh sieve to obtain composite particles; in step B3, the amount ratio of the composite particles, ethanol, saturated sodium hydroxide solution, deionized water and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 8-10g:2-3g:2-3mL:40-60mL:3-5g, and the post-treatment includes: after the reaction is completed, after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the material is constant weight to obtain modified composite particles.

[0034] Furthermore, in step S4, the method for preparing the skin-friendly impregnation liquid comprises the following steps:

[0035] C1. Add the modified composite particles, hyaluronic acid and deionized water into a stirring kettle, stir at room temperature for 20-30 minutes, add silk fibroin into the reaction kettle, raise the temperature of the reaction kettle to 40-50°C, keep warm and stir for 2-4 hours to obtain a dispersion;

[0036] C2. Add the dispersion into a refrigerator at a temperature of 2-4°C and incubate for 1-2 hours to obtain a skin-friendly impregnation solution.

[0037] The reaction principle for preparing the skin-friendly impregnation liquid is as follows: utilizing the property of silk fibroin to self-assemble into a spherical structure at low temperature, introducing modified composite particles having a large number of epoxy groups on the surface into the low-temperature system, utilizing the structure and active organic functional groups to attract the dispersed silk fibroin, so that the silk fibroin uses the modified composite particles as a template to form a spherical structure filled with silk fibroin and coated with the modified composite particles, and finally preparing a dispersion.

[0038] Furthermore, in step C1, the stirring rate of the reactor is 80-120 rpm, and the usage ratio of the modified composite particles, hyaluronic acid, deionized water and silk fibroin is 5-6 g: 0.2-0.3 g: 20-30 mL: 1-2 g.

[0039] The invention discloses an application of an anti-ultraviolet breathable fabric, and the breathable fabric prepared by a method for preparing an anti-ultraviolet breathable fabric is applied to clothing processing.

[0040] The present invention has the following beneficial effects:

[0041] 1. The present invention prepares composite particles with titanium dioxide particles as cores and porous silicon dioxide as shells, wherein a large number of hydroxyl groups on the titanium dioxide particles serve as hydrolysis sites for tetraethoxysilane, so that the silicon dioxide layer produced by hydrolysis is tightly connected to the titanium dioxide core, and the titanium dioxide particles serve as neutral microwave absorbers, and the solvent is evaporated by internal heating, so that the silicon dioxide shell produced by hydrolysis forms a porous stable structure, a protective structure is formed on the surface of the titanium dioxide particles, and polyurethane segments are hybridized after active functional groups are modified on the surface. During the electrostatic spinning process, the titanium dioxide structure inside the segment enhances the electrical conductivity of the material, so that the performance of the modified polyurethane fiber obtained by electrostatic spinning is stable, thereby significantly improving the wear resistance and UV resistance of the material.

[0042] 2. In the process of preparing skin-friendly impregnation liquid, the modified composite particles also act as nucleation centers to promote the self-assembly and filling of silk fibroin at low temperature to form spherical materials. The spherical materials also serve as the main component of the skin-friendly impregnation liquid. In the process of impregnating the modified fabric with the impregnation liquid, due to the swelling property of the polyurethane material, during the microwave evaporation, the impregnation liquid is stably volatilized with titanium dioxide particles as the core, so that the active functional groups on the silk fibroin in the spherical material are cross-linked with the modified fabric to form stable gaps, overcoming the filling of the breathable structure by the modified liquid, and further improving the breathability of the material. The modified composite particles inside significantly enhance the mechanical properties and UV resistance of the material, and the filled silk fibroin significantly enhances the skin affinity and UV resistance of the material, and finally a breathable fabric is obtained.

[0043] 3. The modified composite particles prepared by the present invention have titanium dioxide particles as cores and porous silicon dioxide as shells, and a large number of epoxy groups are modified on the surface thereof. In the process of preparing composite polyurethane, the modified polyurethane chain segments have the structure of UV-13, an anti-ultraviolet ultraviolet absorber, and a large number of epoxy groups on the modified composite particles react with the hydroxyl groups at the ends of the modified polyurethane to form a spatial three-dimensional organic chain segment structure with the modified composite particles as the pivot, thereby significantly enhancing the mechanical strength and anti-ultraviolet performance of the material, and forming a stable conductive network inside the composite polyurethane, so that the modified polyurethane fiber components obtained by electrospinning are uniform and the structure is stable, thereby significantly enhancing the mechanical properties of the material. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] This embodiment provides a method for preparing modified composite particles for anti-ultraviolet breathable fabrics, comprising the following steps:

[0047] Step 1: Preparation of titanium dioxide particles

[0048] Weigh: 36.0g of butyl titanate and 300.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 15min, 160.0mL of deionized water is continued to be added dropwise. After the temperature of the reactor is raised to 50°C, a 1.2mol / L ammonia solution is used to adjust the pH of the system to 8. The mixture is kept warm for 36h to obtain a titanium gel. The titanium gel is added to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 750°C at a heating rate of 3°C / min. After calcination for 4h, the material is ground through an 800-mesh sieve to obtain titanium dioxide particles.

[0049] Step 2: Preparation of composite particles

[0050] Weigh: 12.0g titanium dioxide particles, 30.0g tetraethoxysilane and 300.0mL anhydrous ethanol are added into a reactor and stirred. After stirring at room temperature for 15 minutes, 120.0mL deionized water is continued to be added dropwise. After the temperature of the reactor is raised to 40°C, 1.2mol / L ammonia solution is used to adjust the pH of the system to 8. The mixture is kept warm for 24 hours to obtain a silicon-based gel. The silicon-based gel is transferred to a vacuum microwave device, and the vacuum degree of the device is set to 50mbar, the power is 400W, the stirring rate is 50rpm, and the temperature is controlled to 60°C. After evaporation until no liquid is produced, the material is ground and passed through a 600-mesh sieve to obtain composite particles.

[0051] Step 3: Preparation of modified composite particles

[0052] Weigh: 84.0g of composite particles, 24.0g of ethanol, 24.0mL of saturated sodium hydroxide solution and 400.0mL of deionized water, add them into a reactor and introduce nitrogen protection. After the temperature of the reactor is reduced to 5°C, 36.0g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the reactor. The reaction is kept warm for 20 minutes. After the reaction is completed, after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the material has a constant weight to obtain modified composite particles.

[0053] Example 2

[0054] This embodiment provides a method for preparing modified composite particles for anti-ultraviolet breathable fabrics, comprising the following steps:

[0055] Step 1: Preparation of titanium dioxide particles

[0056] Weigh: 40.0g of butyl titanate and 360.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 120rpm. After stirring at room temperature for 20min, 160.0mL of deionized water is continuously added dropwise. After the temperature of the reactor is raised to 60°C, a 2.0mol / L ammonia solution is used to adjust the pH value of the system to 9. The reaction mixture is kept warm for 48h to obtain a titanium gel. The titanium gel is added to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 850°C at a heating rate of 5°C / min. After calcination for 6h, the material is ground through a 600-mesh sieve to obtain titanium dioxide particles.

[0057] Step 2: Preparation of composite particles

[0058] Weigh: 16.0g titanium dioxide particles, 40.0g tetraethoxysilane and 360.0mL anhydrous ethanol are added to a reactor and stirred. After stirring at room temperature for 20 minutes, 200.0mL deionized water is continued to be added dropwise. After the temperature of the reactor is raised to 60°C, a 1.5mol / L ammonia solution is used to adjust the pH of the system to 9. The mixture is kept warm for 36 hours to obtain a silicon-based gel. The silicon-based gel is transferred to a vacuum microwave device, and the vacuum degree of the device is set to 200mbar, the power is set to 600W, the stirring rate is set to 60rpm, and the temperature is controlled to 80°C. After evaporation until no liquid is produced, the material is ground and passed through a 400-mesh sieve to obtain composite particles.

[0059] Step 3: Preparation of modified composite particles

[0060] Weigh: 96.0g of composite particles, 24.0g of ethanol, 24.0mL of saturated sodium hydroxide solution and 500.0mL of deionized water, add them into a reactor and introduce nitrogen protection. After the temperature of the reactor is reduced to 5°C, 42.0g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the reactor. The reaction is kept warm for 24.0min. After the reaction is completed, after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at 60°C and vacuum dried until the material has a constant weight to obtain modified composite particles.

[0061] Example 3

[0062] This embodiment provides a method for preparing modified composite particles for anti-ultraviolet breathable fabrics, comprising the following steps:

[0063] Step 1: Preparation of titanium dioxide particles

[0064] Weigh: 54.0g of butyl titanate and 400.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 100rpm. After stirring at room temperature for 18min, 160.0mL of deionized water is continued to be added dropwise. After the temperature of the reactor is raised to 55°C, a 1.6mol / L ammonia solution is used to adjust the pH of the system to 9. The mixture is kept warm for 42h to obtain a titanium gel. The titanium gel is added to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 800°C at a heating rate of 4°C / min. After calcination for 5h, the material is ground through a 700-mesh sieve to obtain titanium dioxide particles.

[0065] Step 2: Preparation of composite particles

[0066] Weigh: 18.0g titanium dioxide particles, 48.0g tetraethoxysilane and 360.0mL anhydrous ethanol are added to a reactor and stirred. After stirring at room temperature for 18 minutes, 150.0mL deionized water is continued to be added dropwise. After the temperature of the reactor is raised to 50°C, a 1.2mol / L ammonia solution is used to adjust the pH of the system to 9, and the mixture is kept warm for 30 hours to obtain a silicon-based gel. The silicon-based gel is transferred to a vacuum microwave device, and the vacuum degree of the device is set to 100mbar, the power is set to 500W, the stirring rate is set to 55rpm, and the temperature is controlled to 70°C. After evaporation until no liquid is produced, the material is ground and passed through a 500-mesh sieve to obtain composite particles.

[0067] Step 3: Preparation of modified composite particles

[0068] Weigh: 96.0g of composite particles, 24.0g of ethanol, 24.0mL of saturated sodium hydroxide solution and 500.0mL of deionized water, add them into a reactor and introduce nitrogen protection. After the temperature of the reactor is reduced to 8°C, add 40.0g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane into the reactor and keep the reaction warm for 24 minutes. After the reaction is completed, wait for the temperature of the reactor to rise to room temperature, filter the reaction liquid and collect the filter cake. Place the filter cake in a drying oven at 60°C and vacuum dry it until the material is constant weight to obtain modified composite particles.

[0069] Example 4

[0070] This embodiment provides a method for preparing a composite polyurethane for an anti-ultraviolet breathable fabric, comprising the following steps:

[0071] Step 1: Preparation of modified polyurethane

[0072] Weigh: 36.0 g of UV absorber UV-13, 250.0 mL of N,N-dimethylformamide and 2.4 g of dibutyltin dilaurate are added into a reaction kettle, and stirred at room temperature for 15 minutes to obtain a prepolymer solution;

[0073] Weigh: 10.0 g of 1,3-di(isocyanatomethyl)benzene and 10.0 g of N,N-dimethylformamide to prepare a 1,3-di(isocyanatomethyl)benzene solution;

[0074] Weigh: 200.0 mL of prepolymer solution is added into the reactor, the temperature of the reactor is raised to 50° C., 120.0 g of 1,3-di(isocyanatomethyl)benzene solution is added dropwise into the reactor, and the reaction is carried out at the temperature for 40 minutes. Modified polyurethane is obtained by post-treatment.

[0075] Step 2: Preparation of composite polyurethane

[0076] Weigh: 10.0 g of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 100.0 mL of N,N-dimethylformamide to prepare an anti-ultraviolet liquid;

[0077] Weigh: 80.0g of modified polyurethane, 5.0mL of saturated sodium hydroxide solution and 250.0mL of N,N-dimethylformamide are added to a reactor and stirred at a stirring rate of 80rpm. After the temperature of the reactor is increased to 60°C, 24.0g of the modified composite particles prepared in Example 1 are added to the reactor. After the reaction is kept warm for 20min, 36.0mL of anti-ultraviolet liquid is added to the reactor and the reaction is kept warm for 10min. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a composite polyurethane.

[0078] Example 5

[0079] This embodiment provides a method for preparing a composite polyurethane for an anti-ultraviolet breathable fabric, comprising the following steps:

[0080] Step 1: Preparation of modified polyurethane

[0081] Weigh: 36.0 g of UV absorber UV-13, 280.0 mL of N,N-dimethylformamide and 3.0 g of dibutyltin dilaurate are added into a reaction kettle, and stirred at room temperature for 15 minutes to obtain a prepolymer solution;

[0082] Weigh: 10.0 g of 1,3-di(isocyanatomethyl)benzene and 10.0 g of N,N-dimethylformamide to prepare a 1,3-di(isocyanatomethyl)benzene solution;

[0083] Weigh: 200.0 mL of prepolymer solution is added into the reactor, the temperature of the reactor is raised to 60° C., 124.0 g of 1,3-di(isocyanatomethyl)benzene solution is added dropwise into the reactor, and the reaction is carried out at the temperature for 40-60 min. Modified polyurethane is obtained by post-treatment.

[0084] Step 2: Preparation of composite polyurethane

[0085] Weigh: 10.0 g of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 100.0 mL of N,N-dimethylformamide to prepare an anti-ultraviolet liquid;

[0086] Weigh: 84.0g of modified polyurethane, 6.4mL of saturated sodium hydroxide solution and 250.0mL of N,N-dimethylformamide, add to a reactor and stir at a stirring rate of 120rpm. After the temperature of the reactor is raised to 80°C, 24.0g of the modified composite particles prepared in Example 2 are added to the reactor. After the reaction is kept warm for 24min, 36.0mL of anti-ultraviolet liquid is added to the reactor and the reaction is kept warm for 10min. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a composite polyurethane.

[0087] Example 6

[0088] This embodiment provides a method for preparing a composite polyurethane for an anti-ultraviolet breathable fabric, comprising the following steps:

[0089] Step 1: Preparation of modified polyurethane

[0090] Weigh: 36.0 g of UV absorber UV-13, 260.0 mL of N,N-dimethylformamide and 2.4 g of dibutyltin dilaurate are added into a reaction kettle, and stirred at room temperature for 18 minutes to obtain a prepolymer solution;

[0091] Weigh: 10.0 g of 1,3-di(isocyanatomethyl)benzene and 10.0 g of N,N-dimethylformamide to prepare a 1,3-di(isocyanatomethyl)benzene solution;

[0092] Weigh: 240.0 mL of prepolymer solution was added into the reactor. The temperature of the reactor was raised to 60° C. 135.0 g of 1,3-di(isocyanatomethyl)benzene solution was added dropwise into the reactor. The reaction was kept warm for 50 minutes and modified polyurethane was obtained by post-treatment.

[0093] Step 2: Preparation of composite polyurethane

[0094] Weigh: 10.0 g of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 100.0 mL of N,N-dimethylformamide to prepare an anti-ultraviolet liquid;

[0095] Weigh: 96.0g of modified polyurethane, 7.2mL of saturated sodium hydroxide solution and 250.0mL of N,N-dimethylformamide, add to the reactor and stir at a stirring rate of 100rpm. After the temperature of the reactor is raised to 70°C, 24.0g of the modified composite particles prepared in Example 3 are added to the reactor. After the reaction is kept warm for 25min, 36.0mL of anti-ultraviolet liquid is added to the reactor and the reaction is kept warm for 15min. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a composite polyurethane.

[0096] Example 7

[0097] This embodiment provides a method for preparing an anti-ultraviolet breathable fabric, comprising the following steps:

[0098] S1. Preparation of modified fabrics

[0099] Weigh: 120.0g of the composite polyurethane prepared in Example 4, 20.0g of the modified composite particles, 6.0g of benzalkonium chloride, 7.2g of carbon fiber, 6.4g of dibutyl phthalate and 720.0mL of N,N-dimethylformamide, add them into a reactor and stir, stir for 10min at room temperature to obtain a spinning solution, pour the spinning solution into the ejector of the electrospinning machine, set the voltage of the electrospinning machine to 20kV, set the spinning distance to 20cm, control the flow rate at 0.8L / h, and spin to obtain modified polyurethane fibers;

[0100] 100D modified polyurethane fiber is selected, the number of monofilaments is 36F, the twist of the yarn is set to 500 twists / m, the twist direction is Z twist, and after the twisting is completed, it is heat-set at a temperature of 180°C and wound at a speed of 600m / min to obtain the yarn. The yarns are used as warp yarns and weft yarns, respectively, and the modified polyurethane layer is woven; the imperial count of the warp yarn is 36s, the imperial count of the weft yarn is 35s, the density of the modified polyurethane layer is 160 warp yarns and 100 weft yarns per square inch, and the modified fabric is woven.

[0101] S2. Preparation of breathable fabrics

[0102] Weigh: 54.0 g of the modified composite particles prepared in Example 1, 2.4 g of hyaluronic acid and 24.0 mL of deionized water are added to a stirring kettle, the stirring rate of the reactor is set to 80 rpm, and after stirring at room temperature for 20 min, 12.0 g of silk fibroin is added to the reactor, and after the temperature of the reactor is raised to 40° C., the mixture is stirred for 2 h to obtain a dispersion;

[0103] The dispersion was added to a refrigerator at 4°C and incubated for 1 h to obtain a skin-friendly impregnation solution;

[0104] The modified fabric is immersed in a skin-friendly impregnation liquid, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:20 and an impregnation rate of 90%, and an impregnated material is obtained after the impregnation and rolling are completed;

[0105] The impregnated material was transferred to a vacuum microwave device, and the vacuum degree of the device was set to 200 mbar, the power to 400 W, and the evaporation temperature to 40°C. The impregnated material was evaporated until no liquid was obtained to obtain a breathable fabric.

[0106] Example 8

[0107] This embodiment provides a method for preparing an anti-ultraviolet breathable fabric, comprising the following steps:

[0108] S1. Preparation of modified fabrics

[0109] Weigh: 150.0 g of the composite polyurethane prepared in Example 5, 24.0 g of modified composite particles, 8.0 g of benzalkonium chloride, 8.0 g of carbon fiber, 8.0 g of dibutyl phthalate and 720.0 mL of N,N-dimethylformamide, add them into a reactor and stir, stir for 12 min at room temperature to obtain a spinning solution, pour the spinning solution into the ejector of an electrospinning machine, set the voltage of the electrospinning machine to 25 kV, set the spinning distance to 30 cm, control the flow rate at 1.0 L / h, and spin to obtain modified polyurethane fibers;

[0110] 125D modified polyurethane fiber is selected, the number of monofilaments is 48F, the twist of the yarn is set to 600 twists / m, the twist direction is Z twist, and after the twisting is completed, it is heat-set at a temperature of 200°C and wound at a speed of 700m / min to obtain the yarn. The yarns are used as warp yarns and weft yarns, respectively, and the modified polyurethane layer is woven; the imperial count of the warp yarn is 42s, the imperial count of the weft yarn is 45s, the density of the modified polyurethane layer is 180 warp yarns and 120 weft yarns per square inch, and the modified fabric is woven.

[0111] S2. Preparation of breathable fabrics

[0112] Weigh: 54.0 g of the modified composite particles prepared in Example 2, 2.4 g of hyaluronic acid and 240.0 mL of deionized water are added to a stirring kettle, the stirring rate of the reactor is set to 120 rpm, and after stirring at room temperature for 30 min, 20.0 g of silk fibroin is added to the reactor, and after the temperature of the reactor is raised to 50° C., the mixture is stirred for 4 h to obtain a dispersion;

[0113] The dispersion was added to a refrigerator at 2°C and incubated for 2 h to obtain a skin-friendly impregnation solution;

[0114] The modified fabric is immersed in a skin-friendly impregnation liquid, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:25 and an impregnation rate of 110%, and an impregnation material is obtained after the impregnation and rolling is completed;

[0115] The impregnated material was transferred to a vacuum microwave device, and the vacuum degree of the device was set to 50 mbar, the power to 600 W, and the evaporation temperature to 50°C. The impregnated material was evaporated until no liquid was obtained to obtain a breathable fabric.

[0116] Example 9

[0117] This embodiment provides a method for preparing an anti-ultraviolet breathable fabric, comprising the following steps:.

[0118] S1. Preparation of modified fabrics

[0119] Weigh: 135.0 g of the composite polyurethane prepared in Example 6, 25.0 g of the modified composite particles, 6.4 g of benzalkonium chloride, 7.2 g of carbon fiber, 7.2 g of dibutyl phthalate and 750.0 mL of N,N-dimethylformamide, add them into a reactor and stir, stir for 12 min at room temperature to obtain a spinning solution, pour the spinning solution into the ejector of the electrospinning machine, set the voltage of the electrospinning machine to 24 kV, set the spinning distance to 24 cm, control the flow rate at 0.9 L / h, and spin to obtain modified polyurethane fibers;

[0120] 110D modified polyurethane fiber is selected, the number of monofilaments is 42F, the twist of the yarn is set to 550 twists / m, the twist direction is Z twist, and after twisting, it is heat-set at a temperature of 180°C and wound at a speed of 650m / min to obtain yarn. The yarns are used as warp yarns and weft yarns, respectively, and a modified polyurethane layer is woven. The imperial count of the warp yarn is 40s, and the imperial count of the weft yarn is 36s. The density of the modified polyurethane layer is 160 warp yarns and 110 weft yarns per square inch, and the modified fabric is woven.

[0121] S2. Preparation of breathable fabrics

[0122] Weigh: 54.0 g of the modified composite particles prepared in Example 3, 2.8 g of hyaluronic acid and 240.0 mL of deionized water are added to a stirring kettle, the stirring rate of the reactor is set to 100 rpm, and after stirring at room temperature for 24 min, 18.0 g of silk fibroin is added to the reactor, and after the temperature of the reactor is raised to 45° C., the reactor is stirred for 3 h to obtain a dispersion;

[0123] The dispersion was added to a refrigerator at 3°C ​​and incubated for 2 h to obtain a skin-friendly impregnation solution;

[0124] The modified fabric is immersed in a skin-friendly impregnation liquid, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:24 and a padding rate of 100%, and an impregnated material is obtained after the padding is completed;

[0125] The impregnated material was transferred to a vacuum microwave device, and the vacuum degree of the device was set to 100 mbar, the power to 500 W, and the evaporation temperature to 45°C. The impregnated material was evaporated until no liquid was obtained to obtain a breathable fabric.

[0126] Comparative Example 1

[0127] The difference between this comparative example and Example 9 is that, when preparing the modified composite particles used, step A2 is omitted, and the composite particles in step 3 are replaced by an equal amount of titanium dioxide particles in step 1.

[0128] Comparative Example 2

[0129] The difference between this comparative example and Example 9 is that, when preparing the composite polyurethane used, in step 2, the use of anti-ultraviolet liquid is omitted.

[0130] Comparative Example 3

[0131] The difference between this comparative example and Example 9 is that the use of silk fibroin is omitted in the process of preparing the dispersion in step S2.

[0132] Performance Test:

[0133] The air permeability of the breathable fabrics prepared in Examples 1-3 and Comparative Examples 7-9 was tested with reference to the standard GB / T 5453-1997 "Determination of the anti-ultraviolet performance of textile dyeing and finishing auxiliaries and anti-ultraviolet finishing agents";

[0134] With reference to standard FZ / T 14025-2022 "High Weather-Resistant Polyester Outdoor Fabrics", the ultraviolet protection factor, ultraviolet transmittance, breaking strength and tear strength of the breathable fabrics prepared in Examples 1-3 and Comparative Examples 7-9 were tested (the density of the breathable fabric is 100g / m 2 -150g / m 2 ), see Table 1 for specific data.

[0135] Table 1-Performance test data of each sample

[0136]

[0137] Data Analysis:

[0138] Comparing and analyzing the data in Table 1 above, the air permeability of the breathable fabric prepared by the present invention is 667.25 mm·s -1 , UV protection factor is 61, UV transmittance is 1.0%, warp breaking strength is 351N, weft breaking strength is 301N, warp tear strength is 18.5N and warp tear strength is 12.1N;

[0139] By comparing the data of Example 3 and Comparative Example 1, it can be found that the air permeability and mechanical strength of the breathable fabric are significantly reduced, indicating that the composite particles obtained by hydrolyzing the surface of the titanium dioxide particles and preparing the porous silicon dioxide layer by microwave volatilization of the solvent have significantly improved mechanical properties compared with the titanium dioxide particles, and the porous structure provides excellent air permeability for the fabric;

[0140] By comparing the data of Example 3, Comparative Example 2 and Comparative Example 3, it can be found that the ultraviolet protection ability of the breathable fabric is significantly reduced, indicating that the modification of the polyurethane chain segment by the anti-ultraviolet liquid and the filling of the pore structure of the modified composite material by the silk fibroin are missing, which ultimately leads to the lack of anti-ultraviolet chain segment modification on the polyurethane chain segment and the lack of anti-ultraviolet protein modification in the skin-friendly impregnation liquid, which ultimately significantly reduces the anti-ultraviolet performance of the material;

[0141] The invention prepares composite particles with titanium dioxide particles as cores and porous silicon dioxide as shells, wherein a large number of hydroxyl groups on the titanium dioxide particles serve as hydrolysis sites of tetraethoxysilane, so that the silicon dioxide layer generated by hydrolysis is closely connected with the titanium dioxide core, and the titanium dioxide particles serve as microwave absorbing neutrals, and the solvent is evaporated by internal heating, so that the silicon dioxide shell generated by hydrolysis forms a porous stable structure, and the polyurethane chain segments are hybridized after the active functional groups are modified on the surface of the silicon dioxide shell, and in the process of electrostatic spinning, the titanium dioxide structure inside the chain segments enhances the electrical conductivity of the material, so that the performance of the modified polyurethane fiber obtained by electrostatic spinning is stable; the modified composite particles simultaneously serve as nucleation centers to promote the self-assembly filling of silk fibroin at low temperature to form a spherical material, and the spherical material serves as the main component of a skin-friendly impregnation liquid, and in the process of the impregnation liquid impregnating the modified fabric, due to the swelling property of the polyurethane material, the impregnation liquid is stably volatilized by internal heating during microwave evaporation, so that the active functional groups on the silk fibroin in the spherical material are cross-linked with the modified fabric to form stable gaps, and finally a breathable fabric is obtained.

[0142] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing an anti-ultraviolet breathable fabric, characterized in that: The following steps are involved: S1. Add modified polyurethane, saturated sodium hydroxide solution and N,N-dimethylformamide into a reactor and stir. After the temperature of the reactor is raised to 60-80°C, add modified composite particles into the reactor, keep warm for 20-30 minutes, add anti-ultraviolet liquid into the reactor, keep warm for 10-20 minutes, and post-treat to obtain composite polyurethane, wherein the anti-ultraviolet liquid is prepared from 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and N,N-dimethylformamide at a dosage ratio of 1g:10mL; S2, adding composite polyurethane, auxiliary materials and N,N-dimethylformamide into a reaction kettle and stirring, stirring at room temperature for 10-15 minutes to obtain a spinning solution, and using the spinning solution for electrospinning to obtain modified polyurethane fibers; S3, using the modified polyurethane fiber for weaving to obtain a modified fabric; S4, soaking the modified fabric in a skin-friendly impregnation liquid, obtaining an impregnated material after padding, and obtaining a breathable fabric by a microwave evaporation process; The preparation method of modified polyurethane comprises the following steps: A1. Add UV absorber UV-13, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stir for 15-20 minutes at room temperature to obtain a prepolymer solution; A2, adding the prepolymer liquid into the reactor, raising the temperature of the reactor to 50-60°C, dropping 1,3-di(isocyanatomethyl)benzene solution into the reactor, keeping the temperature for reaction for 40-60min, and post-treating to obtain modified polyurethane; The preparation method of the modified composite particles comprises the following steps: B1. Add butyl titanate and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 50-60°C, use 1-2 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep the temperature for 36-48 hours to obtain titanium gel, and then post-treat to obtain titanium dioxide particles. B2. Add titanium dioxide particles, tetraethoxysilane and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep the temperature for 24-36 hours to obtain a silicon-based gel, and then perform post-treatment to obtain composite particles. B3, adding composite particles, ethanol, saturated sodium hydroxide solution and deionized water into a reactor and introducing nitrogen protection, after the temperature of the reactor is reduced to 5-10° C., adding 3-(2,3-epoxypropoxy)propyltrimethoxysilane into the reactor, keeping the temperature for reaction for 20-30 minutes, and post-treating to obtain modified composite particles; The preparation method of the skin-friendly impregnation liquid comprises the following steps: C1. Add the modified composite particles, hyaluronic acid and deionized water into a stirring kettle, stir at room temperature for 20-30 minutes, add silk fibroin into the reaction kettle, raise the temperature of the reaction kettle to 40-50°C, keep warm and stir for 2-4 hours to obtain a dispersion; C2. Add the dispersion into a refrigerator at a temperature of 2-4°C and incubate for 1-2 hours to obtain a skin-friendly impregnation solution.

2. The method for preparing a UV-resistant breathable fabric according to claim 1, characterized in that: In step S1, the usage ratio of modified polyurethane, saturated sodium hydroxide solution, N,N-dimethylformamide, modified composite particles and anti-ultraviolet liquid is 8-10g:0.5-0.8mL:25-30mL:2-3g:3-5mL, and the stirring rate of the reactor is 80-120rpm.

3. The method for preparing a UV-resistant breathable fabric according to claim 1, characterized in that: In step A1, the amount ratio of ultraviolet absorber UV-13, N,N-dimethylformamide and dibutyltin dilaurate is 4-5g:25-30mL:0.1-0.3g, and the stirring rate of the reactor is 80-120rpm; in step A2, the amount ratio of prepolymer liquid and 1,3-di(isocyanatomethyl)benzene solution is 20-25mL:12-15g, and 1,3-di(isocyanatomethyl)benzene solution is prepared by 1,3-di(isocyanatomethyl)benzene and N,N-dimethylformamide in a weight ratio of 1:

1.

4. The method for preparing an anti-ultraviolet breathable fabric according to claim 1, characterized in that: In step B1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of butyl titanate, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL; in step B2, the amount ratio of titanium dioxide particles, tetraethoxysilane, anhydrous ethanol and deionized water is 1-2g:3-6g:30-40mL:10-20mL, and the stirring rate of the reactor is 60-80rpm; in step B3, the amount ratio of composite particles, ethanol, saturated sodium hydroxide solution, deionized water and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 8-10g:2-3g:2-3mL:40-60mL:3-5g.

5. The method for preparing an anti-ultraviolet breathable fabric according to claim 1, characterized in that: In step C1, the stirring rate of the reactor is 80-120 rpm, and the usage ratio of the modified composite particles, hyaluronic acid, deionized water and silk fibroin is 5-6 g: 0.2-0.3 g: 20-30 mL: 1-2 g.

6. An application of an anti-ultraviolet breathable fabric, characterized in that: The breathable fabric prepared by the method for preparing an anti-ultraviolet breathable fabric according to any one of claims 1 to 5 is applied to clothing processing.

Citation Information

Patent Citations

  • Preparation method of modified nano TiO2 / epoxy-polyurethane ternary composite material

    CN108774304A

  • Polyurethane elastomer for low-temperature-resistant shoe material and preparation process of polyurethane elastomer

    CN115304737A

Cited By

  • High-dose ultraviolet protection fabric and preparation method thereof

    CN120867093A